Assessing Parents' Treatment Fidelity: A Survey of Practitioners in Home Settings. (March 2020) - Fallon, Lindsay M.; Cathcart, Sadie C.; Sanetti, Lisa M. Hagermoser
Children with autism spectrum disorder (ASD) and other developmental disabilities may benefit from home-based interventions to promote positive, prosocial behavior. Frequently, a practitioner (e.g., behavior analyst) provides training and support to parents to achieve behavior change. When this occurs, progress-monitoring data pertaining to both treatment fidelity and child outcomes are important to deciding if supports delivered are effective. Yet, little is known about treatment fidelity assessment in this setting. In the current study, behavior analysts working across the United States in homes ( n = 314) were surveyed. Results indicate that nearly all participants reported having received some or extensive training on the importance of treatment fidelity. Most respondents also indicated that treatment fidelity is assessed in at least 30% of sessions in homes when working with parents, primarily by means of direct observation versus indirect methods. Implications for future consultation research and the practice are provided.